2003
DOI: 10.1021/pr034020m
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Metabolome Analysis Using Capillary Electrophoresis Mass Spectrometry

Abstract: A new approach for the comprehensive and quantitative analysis of charged metabolites by capillary electrophoresis mass spectrometry (CE-MS) is proposed. Metabolites are first separated by CE based on charge and size and then selectively detected using MS by monitoring over a large range of m/z values. This method enabled the determination of 352 metabolic standards and its utility was demonstrated in the analysis of 1692 metabolites from Bacillus subtilis extracts, revealing significant changes in metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
683
0
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 904 publications
(697 citation statements)
references
References 28 publications
6
683
0
8
Order By: Relevance
“…In this study, the Biolog phenotyping dataset could be used effectively for the metabolic reconstruction of B. subtilis, and furthermore the latter could enhance the quality and utility of the former (see above). However, the in silico model could only predict 46% (160 in 350) of the experimental metabolomic compounds reported from the literature (5). At the present time, the annotation of the B. subtilis genome is incomplete, and ϳ40% of its ORFs do not have a functional assignment (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the Biolog phenotyping dataset could be used effectively for the metabolic reconstruction of B. subtilis, and furthermore the latter could enhance the quality and utility of the former (see above). However, the in silico model could only predict 46% (160 in 350) of the experimental metabolomic compounds reported from the literature (5). At the present time, the annotation of the B. subtilis genome is incomplete, and ϳ40% of its ORFs do not have a functional assignment (2).…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noticed that subtle differences in the experimental conditions and the strain background could induce the difference between lethal and a very slow growth mutation (22). The in silico metabolites of the metabolic network were also compared with experimental metabolomic data for B. subtilis grown in a moderately rich medium (5). 350 of 1692 compounds separated have been positively identified using standards (see supplemental Table 1 of Ref.…”
Section: Table 2 Impact Of Single-gene Deletions On Growth In B Subtmentioning
confidence: 99%
“…After the centrifugation, the supernatant was filtered (M r cutoff of 5,000) and lyophilized, and the resulting dried extract was dissolved in 20 l of water. Capillary electrophoresis electrospray ionization time-of-flight mass spectrometry (CE-TOFMS) measurements were performed as described previously (27,28,29). In this procedure, the recovery rates of nucleotides ranged from 60 to 90%, for example, 76, 81, 82, 63, 84, 76, 89, 57, and 66% for AMP, ADP, ATP, dATP, UDP, GDP, CDP, dTDP, and ppGpp, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Application of metabolomic analyses using capillary electrophoresis/electrospray ionization/mass spectrometry (CE/ESI/MS; refs. 21,22) allows us to determine fluxes of multiple metabolic pathways during cell-cycle progression in vitro (20,23,24). MALDI-IMS analyses of metastatic tumors have shown that the cancer cells in G 1 phase were more active in glycolysis than those in the other phases.…”
Section: Introductionmentioning
confidence: 99%